Evolution of nanostructured single-phase CoSb3 thin films by low-energy ion beam induced mixing and their thermoelectric performance. Issue 36 (4th September 2017) - Bala, Manju; Gupta, Srashti; Srivastava, Sanjeev K.; Amrithapandian, Sankarakumar; Tripathi, Tripurari S.; Tripathi, Surya K.; Dong, Chung-Li; Chen, Chi-Liang; Avasthi, Devesh K.; Asokan, Kandasami
Abstract : We report that a nanostructured CoSb3 thin film in a single phase can be synthesized by ion beam processing of Co/Sb bilayer thin films with better thermoelectric properties. Abstract : Skutterudites are emerging as potential candidates that show high efficiency and thus provide an ideal platform for research. The properties of nanostructured films of skutterudites are different from those of the corresponding bulk. The present study reports the evolution of nanostructured single-phase CoSb3 fabricated by using low-energy ion irradiation of Co/Sb bilayer films and subsequent annealing at an optimized temperature and their Seebeck coefficients ( S ). The effects of ion beam parameters with annealing on the phase evolution and nanostructure modifications were studied. An increase in Xe + ion fluence resulted in complete mixing of Co/Sb on postannealing forming flower-like nanostructures of single phase CoSb3 . The temperature-dependent electrical resistivity ( ρ ) increases with the ion fluence because of defect creation which further increases on postannealing due to surface nanostructuring. The S of these films of CoSb3 is found to be higher and this is attributed to the formation of a uniform layer of nanostructured CoSb3 alloy thin film. The S and Hall coefficients of all these films are negative implying that they are n-type semiconductors.